PENGARUH BRAND IMAGE DAN COUNTRY OF ORIGIN IMAGE TERHADAP MINAT PEMBELIAN IPHONE - Kitto Hananto (Parsimonia - Jurnal Ekonomi dan Bisnis, 2015)
This research is motivated by the development of globalization, rapidly affecting the growth of smartphone users. Through this study, the researchers expected to analyze the effect from brand image and the image of the country of origin on Iphone buying interest in the city of Malang. The method used is explanatory research method. The type of data in this research is quantitative. The approach used is to use a questionnaire distributed through google docs. Sources of data in this study were 200 respondents who are students in the city of Malang. Testing the validity of the data used validity and reliability testing. Based on the results of the research showed that the brand image and the country of origin image has direct and significant effect on the interest on student Iphone purchases in the city of Malang. Besides brand image and the country of origin image have partial effect on the interest in the Iphone purchase. Further also that Brand image obtained more dominant effect on the interest in purchasing the Iphone than the country of origin.